Molecular interplay between ecdysone receptor and retinoid X receptor in regulating the molting of the Chinese mitten crab, Eriocheir sinensis - Chen, Xiaowen; Hou, Xin; Yang, Hao; Liu, Hao; Wang, Jun; Wang, Chenghui (Frontiers in Endocrinology, 2023)
Molting is a pivotal biological process regulated by the ecdysteroid signaling pathway that requires molecular coordination of two transcription factors, Ecdysone receptor (EcR) and ultraspiracle (USP) in arthropods. However, the molecular interplay of EcR and Retinoid X receptor (RXR), the crustacean homolog of USP in the ecdysteroid signaling pathway, is not well understood. In this study, we conducted temporal and spatial expression, coimmunoprecipitation (CO-IP), and luciferase reporter assay experiments to investigate the molecular function and interplay of EcR and RXR during the molting process of the Chinese mitten crab, Eriocheir sinensis. The results showed that the expression level of RXR was more stable and significantly higher than EcR during the entire molting process. However, the expression level of EcR fluctuated dynamically and increased sharply at the premolt stage. The CO-IP and luciferase reporter assay results confirmed the molecular interplay of EcR and RXR.The heterodimer complex formed by the two transcription factors significantly induced the transcription of E75, an essential gene in the ecdysteroid signaling pathway. Our study unveiled the diverse molecular function and molecular interplay of EcR and RXR; RXR is possibly a "constitutive-type" gene, and EcR is possibly a vital speed-limiting gene while both EcR and RXR are required to initiate the ecdysteroid signaling cascade, which may be indispensable for molting regulation in E. sinensis. The results provide a theoretical basis for the endocrine control of molting in E. sinensis and novel insights into the molecular mechanism of molting mediated by the ecdysteroid signaling pathway in crustaceans.